SOILS OF THE OLPILAK RIVER REGION, ALASKA. - Brown,Jerry (1966)
Concepts of Arctic pedology are applied to the glaciated and unglaciated terrains in the vicinity of the Okpilak River, northeastern Alaska. Two types of frost action in Arctic soils are considered: (1) the surficial configurations or patterned ground, and (2) the morphological characteristics of the seasonally thawed soil and the upper zone of perennially frozen ground. About 55 types of soil conditions and surface features are described and mapped in an area encompassing both the northern Brooks Range and the southern Foothill Provinces. These include the genetic soils of Arctic Alaska, numerous soil conditions, and many of the common sorted and nonsorted circles, nets, polygons, steps, and stripes. In the glaciated and periglacial areas, sorted features predominate on the coars-textured substrata. The Arctic brown soils are distributed on the well-drained sites along valley traverses and across mountain gradients. On a sequence of valley moraines, acid parent material is considered more important than time and mesoenvironments in influencing the depth and development of the characteristic brown solum. Weakening of the soil-forming processes with increasing altitude is suggested in the mountains. In the valleys, a podzol-like soil is observed in close proximity to the Arctic brown soils and in association with acid parent materials, dwarf birch-heath vegetation and protected microrelief positions. A combination of peaty soils associated with icewedge polygons constitutes an organic terrain. The developments of these soils under the Arctic environment are discussed. (Author)